An Improved Of Dual Single Input Fuzzy Logic Controller For Underwater Remotely Operated Vehicle (ROV) – Depth Control - Mohd Aras, Mohd Shahrieel; Aripin, Muhamad Khairi; Harun, Mohamad Haniff; Husni @ Rusli, Ahmad Faiez; Sulaiman, Marizan; Nor Azmi, Muhammad Wahyuddin; Rizman, Z. I. (University of El Oued, 2018)
This paper presents an improvement of Dual Single Input Fuzzy Logic Controller (DSIFLC) of an underwater Remotely Operated Vehicle (ROV) system for depth control. Proportional Integral Derivative (PID) controller are used as the basic controller and compared with the SIFLC controller.The technique used is the conventional Fuzzy Logic Controller simplified to Single Input Fuzzy Logic Controller (SIFLC) by using signed distance method.The SIFLC were upgraded to DSIFLC by using double feedback of disturbance.The controller was upgraded until the system response shows the satisfied result in terms of rise time and percentage of overshoot.This method was verified and validated in MATLAB/Simulink platform.The result shows it was found the proposed method have better performances analysis of the system response which is faster rise time and lower percentage of overshoot.